Acute Kidney Injury and Early Predictive Factors in COVID-19 Patients - Liu, Jiaye; Wang, Tingyan; Cai, Qingxian; Huang, Deliang; Sun, Liqin; He, Qing; Wang, Fu-Sheng; Chen, Jun (Frontiers in Medicine, 2021)
Objectives To explore the incidence and early predictive factors of acute kidney injury in coronavirus disease 2019 (COVID-19) patients. Method We established a retrospective cohort of 408 patients who were admitted to Shenzhen Third People’s Hospital in Shenzhen, China, between January 1 and March 31, 2020. Clinical outcomes and renal function were monitored until April 12, 2020, with a median follow-up duration of 21 days (interquartile range [IQR]: 14-33). Results When first admitted to hospital (baseline), 19.36% (79/408) presented renal dysfunction (estimated glomerular filtration [eGFR] < 90 ml/min/1.73 m2). During follow-up, 3.9% (16/408) developed acute kidney injury (AKI). Age ≥ 60 years (hazard ratio [HR] 4.78, 95% CI 1.10-20.69), PaO2/FiO2 ratio < 300 (HR 3.48, 95% CI 1.04-11.62), and higher creatinine (HR 1.04, 95% CI 1.01-1.07) at baseline independently predicted the risk of AKI. 25.0% (102/408), 3.9% (16/408), 0.5% (2/408), 1.0% (4/408), and 0.2% (1/408) respectively experienced G2, G3a, G3b, G4, and G5 as their severest category during hospitalization, while 69.4% (283/408) had normal eGFR throughout the follow-up period. When finally discharged from hospital, there were 12.5% (51/408) of patients with abnormal eGFR. Conclusions COVID-19 patients can be at risk of AKI and continuous eGFR decline during hospitalization, which can be early predicted by baseline factors. Some individuals still had renal dysfunction when finally discharged from hospital.